A two-way bilingual model for elementary school. (1st January 2000) - McDonough, Ellen
This paper describes a multi-media project designed to help parents understand a specific bilingual program at the elementary school level. The main goal of the project is to describe the two-way bilingual model in use at the Bailey School.